Impact of COVID-19 Control Measures on Trace Gases (NO2, HCHO and SO2) and Aerosols over India during Pre-monsoon of 2020 - Mriganka Sekhar Biswas; D. C. Ayantika (Aerosol and Air Quality Research)
Abstract To prevent the transmission of COVID-19, India implemented country-wide restrictions on socio-economic activities. Using satellite observations for the pre-monsoon (March–April–May) season, we explore the effect of the extended lockdown, on nitrogen dioxide (NO2), formaldehyde (HCHO), sulfur dioxide (SO2) and aerosol optical depth (AOD) over India. In this present study we evaluate and quantify the changes in pollutants across six different geographical zones along with the six most populous cities in the country. During April–May the lockdown have resulted in a net decrease in NO2 column density over India in 2020 compared to 2017–2019 average for the same months. Maximum average seasonal reduction of both NO2 (−5.6%) and HCHO (−1.3%) occurred over southern India (SI). Compared to March and April, anomalous HCHO for all the regions decreased in May. Anomalous surface cooling induced lower volatile organic carbons (VOCs) emission and slower VOC oxidation due to absence of high nitric oxide led to decrease in HCHO. A reduction in NO2 was also seen over the top six populous Indian cities, with Mumbai recording the highest decrease (−33.7%). But only Chennai showed a substantial decrease (−6.8%) in HCHO. A significant seasonal reduction in SO2 was noted over western India (WI) and SI. Additionally, widespread decline covering all the zones was found in the pre-monsoon AOD. In April, the decrease occurred primarily over the Indo-Gangetic-Plains (IGP) and eastern India, while in May a marked homogeneous reduction was noted over entire India. Aerosol induced attenuation of incident solar radiation leads to concurrent changes in MERRA2 insolation during pre-monsoon of 2020. Furthermore, reduced anthropogenic aerosols resulted in reduction of availed cloud condensation nuclei (CCN) leading to larger cloud droplet size and hence increased precipitation during pre-monsoon, 2020.